North Eastern Council Annual Plan 1994-95 - Planning Commission (Planning Commission, 1994)
The North Eastern Region has been geographically isolated from the rest of the country in the sense the it 98% of the total perimeter of the region is international border while only 2% of the border connects with the rest of the country. Most of the international border is not a natural border but an artificially created one. It has therefore, in the process eliminated the existing trade, commerce and other communication links with the erstwhile integrated British India. the whole region has become landlocked. the North Eastern Region is linked with the mainland of the country through a narrow corridor, the so-called chicken’s neck.
North Eastern Council Secretariat, Ministry of Home Affairs, Government of India, Shillong